2020
DOI: 10.31234/osf.io/wg4bj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Working with Bipolar Disorder During the COVID-19 Pandemic: Both Crisis and Opportunity

Abstract: Beyond public health and economic costs, the COVID-19 pandemic adds strain, disrupts daily routines, and complicates mental health and medical service delivery for those with mental health and medical conditions. Bipolar disorder can increase vulnerability to infection; it can also enhance stress, complicate treatment, and heighten interpersonal stigma. Yet there are successes when people proactively improve social connections, prioritize self-care, and learn to use mobile and telehealth effectively.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Much like Stefana et al ( 2020 ) and Youngstrom et al ( 2020 ), we are convinced that every crisis could be an opportunity by learning and rethinking and therefore gaining a more in-depth understanding of BD patients’ special needs during the pandemic.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Much like Stefana et al ( 2020 ) and Youngstrom et al ( 2020 ), we are convinced that every crisis could be an opportunity by learning and rethinking and therefore gaining a more in-depth understanding of BD patients’ special needs during the pandemic.…”
Section: Discussionmentioning
confidence: 86%
“…In psychiatric samples, lockdown measures including temporary shutdown of medical and mental health treatment and the disrupted rhythm of a healthy life, such as reduced opportunities to exercise, experience sunlight exposure, and participate in meaningful activities, could pose a special risk or relapse during the pandemic (Muruganandam et al 2020 ; Youngstrom et al 2020 ). Hao et al ( 2020 ) confirmed that patients with psychiatric disorders experienced more psychiatric symptoms during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 global health crisis is a disaster; however, it can also be an opportunity (Stefana et al, 2020c ; Youngstrom et al, 2020 ) to improve health care systems and services by including an increased number of NICU staff members, adequate resources and training, and improved visitation policies for family members of hospitalized infants. Before the COVID-19 pandemic, there was a widespread and substantial shortage of NICU medical and nursing staff (Rogowski et al, 2013 ; Gagliardi et al, 2016 ; Bliss, 2017 ) the current crisis has highlighted.…”
Section: Supporting Persons and Strengthening Nicusmentioning
confidence: 99%
“…[28] Finally, these subjects are likely to face a double stigma stemming from their mental and health problems. [27] We need to reconsider novel ways to facilitate access to therapeutic interventions for this patient population. Faceto-face visits could be replaced by telehealth solutions that facilitate assessment, monitoring, diagnosis, and treatment, including issuing prescriptions.…”
Section: Bipolar and Related Disordersmentioning
confidence: 99%